Deconstruction of organised crime and research of war victimisation - Simeunović-Patić Biljana; Nikolić-Ristanović Vesna (Temida, 2024)
There are many indications that various aspects and factors of large-scale war victimization could be made visible through the collection and analyses of data on organized crime in post-conflict societies. War victimisation could be understood as an outcome of opportunistic criminal activity: war conditions offer the unique opportunity to criminals and criminal groups (especially those involved in military or paramilitary formations) not only to restrain their destructive personal potentials but also to attain a new identity as ’national heroes’ and gain a significantly better economic position as advantageous ’investments’ to post-war criminal business. Crimes in war as well as war crimes, often perceived as basically launched by nationalistic (‘blood and belonging’) ideology, could be examined from a broader hypothetical framework: nationalist ideologies should be considered not only as drives but also as means. By identifying themselves primarily as members of a specific nation who ’defend’ (or victimize) a specific ethnic group, criminals of war provide not only the legitimization of crimes against other nations/ethnic groups but also of crimes against (primarily political) opponents within their ethnic group. The main aim of this paper is to argue for research on the continuity of organised criminal activities before, during and after ethnic conflicts in the Former Yugoslavia. This kind of research is argued to be a promising tool for the assessment of links between war and organized crime victimization as a way of getting a more comprehensive picture of the recent past. Research findings may further be used as the basis for creating comprehensive regional security strategies. Moreover, although the focus of this paper is on organised crime committed during the wars on the territory of the former Yugoslavia, its analyses and conclusions may be applicable to other similar contexts, including contemporary armed conflicts in different parts of the world.